2012
DOI: 10.1159/000339928
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Cystic Fibrosis-Related Diabetes Two Years after Lung Transplantation

Abstract: Background: Although transplantation is known to impair glucose tolerance, evolution of pre-existing diabetes after lung transplantation (LT) in cystic fibrosis (CF) has never been described. Objectives: We aimed to assess the outcome of CF-related diabetes (CFRD) after LT, with the hypothesis that suppressing chronic inflammatory foci may improve glucose tolerance in some patients. Methods: In a retrospective study of 29 CF diabetic patients treated with insulin and undergoing LT, CFRD control was assessed 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…However, it further indicates that F508del is associated with elevated 1-h glucose values and that also males are affected by pre-diabetic conditions, mainly IFG. As expected, any transplantation, nutritional supplementation, and/or steroid use were related to increased rates of glucose tolerance abnormalities due to the effect of anti-inflammatory/immunosuppressive medication on postprandial insulin sensitivity [22,26] or the potential contribution of enteral/parenteral nutrition to postprandial hyperglycemia.…”
Section: Discussionsupporting
confidence: 65%
“…However, it further indicates that F508del is associated with elevated 1-h glucose values and that also males are affected by pre-diabetic conditions, mainly IFG. As expected, any transplantation, nutritional supplementation, and/or steroid use were related to increased rates of glucose tolerance abnormalities due to the effect of anti-inflammatory/immunosuppressive medication on postprandial insulin sensitivity [22,26] or the potential contribution of enteral/parenteral nutrition to postprandial hyperglycemia.…”
Section: Discussionsupporting
confidence: 65%
“…Lung transplantation does not appear to increase the risk of diabetes in CF patients compared with non-CF transplant patients [25]; however glycaemic control deteriorates in the majority of CFRD patients following transplantation [26].…”
Section: Cfrd Current Managementmentioning
confidence: 95%
“…Valour et al published a retrospective study investigating the course of pre‐existing CFRD after LT and found better control of CFRD in two‐thirds of patients. They proposed that the improvement of insulin sensitivity was related to the reduction in systemic inflammation related to chronic pulmonary infection . In some studies, pre‐existing CFRD or development after LT did not appear to be associated with worse outcomes; Hofer et al even found a trend toward better survival after LT in patients with CFRD.…”
Section: Cf‐related Diabetesmentioning
confidence: 99%
“…They proposed that the improvement of insulin sensitivity was related to the reduction in systemic inflammation related to chronic pulmonary infection. 23 In some studies, pre-existing CFRD or development after LT did not appear to be associated with worse outcomes 18,24 ; Hofer et al 25 even found a trend toward better survival after LT in patients with CFRD. However, in several studies, the mortality in patients with CF appears higher among those with CFRD diagnosed before LT compared to those without.…”
mentioning
confidence: 96%